2015
DOI: 10.1080/10255842.2015.1069547
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of centers of mass of body segments with the gravity line

Abstract: a arts et metiers paristech, lBm/institut de Biomecanique humaine georges Charpak, paris, France; b department of orthopedic surgery, nYu hospital for Joint diseases, new York, nY, usa; c umr_t9406, lBmC laboratoire de Biomécanique et mécanique des Chocs, iFsttar, Bron, France

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The pioneering work of Duval Beaup ere et al has shown the relevance of spine and body balance when characterizing scoliosis [3]. More recently, the analysis of gravitational parameters such as the gravity line or the center of mass (COM) could be obtained from biplanar radiographs by estimating the mass distribution in different regions of the body to evaluate its segmental balance [4]. These estimations were obtained using force platform in standing position [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering work of Duval Beaup ere et al has shown the relevance of spine and body balance when characterizing scoliosis [3]. More recently, the analysis of gravitational parameters such as the gravity line or the center of mass (COM) could be obtained from biplanar radiographs by estimating the mass distribution in different regions of the body to evaluate its segmental balance [4]. These estimations were obtained using force platform in standing position [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Methods were proposed to obtain the patient's external envelope in standing position from biplanar radiographs [9]. It has been shown that with such methods, it is possible to accurately estimate the position of body COM both in healthy and scoliotic patients by estimating the density of each body segment [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…The individuals having Sway back posture present with anterior balance strategy as they have anteriorly swayed pelvis in reference to Plumb line. C. Amabile et al [20] studied the sagittal alignment of centers of mass of body segments with the gravity line in asymptomatic young adults by using a bi-planar X-ray system combined with 3D reconstruction of the external body shape for computation of the body segments Center of Mass (COM). The segments superior to femoral heads were found to be anterior to the Gravity Line.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, reconstruction of the external envelope associated with density models allows an estimation of mass and the centre of mass of each body segment (Amabile et al, 2016). Computation of the barycentre of the body segment above a given joint allows estimation of the gravitational load taking into account subject-specific posture (Amabile et al, 2015). The clinical relevance of this barycentremetric approach has been assessed in the study of idiopathic scoliosis (Thenard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%